The Habitus of Care in Medical Research: A Relational Interpretation of the Foundational Assumptions of Bioethics - Bartkienė, Aistė; Mincytė, Diana; Rinkevičius, Leonardas (Problemos, 2014)
This article explores the assumptions behind the principle of respect for patient autonomy that occupies an important role in bioethical research. Relying on the works of L. Dumont and C. Geertz we show how the principle of respect for patient autonomy is related to the concept of personhood, which stems from the Western, Christian, and individualistic values. In so doing, we argue that this principle is bound to overemphasize rationality, as is the case in the extensive use of informed consent forms in modern medical practice. We propose to apply normative ideals of care defined by Nel Noddings to the sphere of bioethics by linking it to Pierre Bourdieu’s notion of habitus in the field of medicine. An incorporation of habitus into ethics of care is useful because it highlights the ways in which interpersonal relations relate to one’s moral development and points to the significance of sociocultural and historical contexts in shaping behaviors.
Keywords: bioethics; autonomy; individualism; ethics of care; habitus